26=3u-64

Simple and best practice solution for 26=3u-64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=3u-64 equation:


Simplifying
26 = 3u + -64

Reorder the terms:
26 = -64 + 3u

Solving
26 = -64 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
26 + -3u = -64 + 3u + -3u

Combine like terms: 3u + -3u = 0
26 + -3u = -64 + 0
26 + -3u = -64

Add '-26' to each side of the equation.
26 + -26 + -3u = -64 + -26

Combine like terms: 26 + -26 = 0
0 + -3u = -64 + -26
-3u = -64 + -26

Combine like terms: -64 + -26 = -90
-3u = -90

Divide each side by '-3'.
u = 30

Simplifying
u = 30

See similar equations:

| E^3-2x=10 | | 2y+4=4y-6 | | 38k=2204 | | 60x-40=50x | | 6x-1+8x=3x+3-5x | | 19y=95 | | g+11=-3 | | 2x-8x+6=19 | | 363-x=-201 | | 4x=10+y | | 3(x-1)+x=4x+2 | | (2x-1)*(2x+1)= | | logpq=r | | U=233+37n | | 10x+90=20x+120 | | (3x+1/2x-3)=(6x-5/4x+7) | | -55-p= | | U=7(4n+32)+9(n+1) | | 3(4x+1)-5=2y+3x-6 | | x-(x*0.1)=1.12 | | 160+0.25x=325 | | y=x*x-8x+15 | | X-3(2X+3)=8.5X | | -4(2x-4)+3x-4=37 | | 10+73=8x+191 | | a=1-2-2-2-3-3-4-5-6-7 | | (6u-3v+1)(3u+v)=0 | | c^2+8=0 | | -6+y=75 | | 5+7=-3 | | 3,75x=2,50x+20 | | (6-7i)(8-3i)=0 |

Equations solver categories